2010
DOI: 10.1007/s11121-010-0191-4
|View full text |Cite
|
Sign up to set email alerts
|

Social Networking Technology, Social Network Composition, and Reductions in Substance Use Among Homeless Adolescents

Abstract: Peer-based prevention programs for homeless youth are complicated by the potential for reinforcing high-risk behaviors among participants. The goal of this study is to understand how homeless youth could be linked to positive peers in prevention programming by understanding where in social and physical space positive peers for homeless youth are located, how these ties are associated with substance use, and the role of social networking technologies (e.g., internet and cell phones) in this process. Personal so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 49 publications
5
93
1
2
Order By: Relevance
“…Another recent study of similarly aged homeless youth found alcohol and marijuana usage rates of 69% and 58%, respectively, whereas lifetime methamphetamine use and cocaine use were 34% and 30%, respectively (Rice et al, 2011). These prevalence rates of substance use are generally consistent with older literature on homeless youth (Greene et al, 1997).…”
Section: Prevalence Of Substance Usesupporting
confidence: 76%
“…Another recent study of similarly aged homeless youth found alcohol and marijuana usage rates of 69% and 58%, respectively, whereas lifetime methamphetamine use and cocaine use were 34% and 30%, respectively (Rice et al, 2011). These prevalence rates of substance use are generally consistent with older literature on homeless youth (Greene et al, 1997).…”
Section: Prevalence Of Substance Usesupporting
confidence: 76%
“…Research finds that homeless youth have high rates of illicit drug use (Hadland et al, 2011;Hagan & McCarthy, 1997;Rice, Milburn, & Monro, 2011). Risk factors for substance use among this population include physical and/or sexual abuse (Gallupe & Baron, 2009;Kipke, Montgomery, & MacKenzie, 1993;Tyler, Gervais, & Davidson, 2013), lower selfefficacy (Gallupe & Baron, 2009), deviant values (Baron, 2003), being a victim of partner violence (Salomon, Bassuk, & Huntington, 2002;Tyler, Melander, & Noel, 2009), posttraumatic stress disorder (PTSD; Johnson, Whitbeck, & Hoyt, 2005), and depression (Hadland et al, 2011;Slesnick et al, 2009).…”
Section: Illicit Drug Usementioning
confidence: 99%
“…Inoltre, la presenza di familiari nella rete e di membri con un livello di istruzione elevato costituiva un fattore protettivo dall'uso di sostanze. Rhoades et al [2011] hanno analizzato le reti sociali di senzatetto uomini al fine di identificare i fattori che predicono l'uso di droga in questa categoria di soggetti, e hanno scoperto che l'alta proporzione di membri della rete che consumavano sostanze era associata all'assunzione di droghe, corroborando i risultati di precedenti studi che hanno sottolineato la correlazione tra i legami substance using e il consumo individuale di droga [Wenzel et al, 2009;Rice et al, 2011].…”
Section: Un Excursus Degli Studi In Letteratura: Social Network E Counclassified